WUJUD PRAGMATIK KESANTUNAN IMPERATIF DALAM PROSES PEMBELAJARAN SISWA KELAS VIII SMP NEGERI 1 PONDOK KELAPA BENGKULU TENGAH - Retno Esti Nugraheni (Wacana: Jurnal Penelitian Bahasa, Sastra dan Pengajaran, 2017)
This study aimed to describe a form of politeness pragmatic imperative in the learning process of students in class VIII SMP Negeri 1 Pondok Kelapa Central Bengkulu. This research is a qualitative description. The data in this study is data in the form of verbal utterances in students' interaction with students, and students and teachers in the classroom environment of SMP Negeri 1 Pondok Kelapa Central Bengkulu. The collection of data by observation, recording, and recording. Analyzing data with several stages of the (1) transcription of data, (2) the encoding of data, (3) identification of the data, (4) the classification of data, (5) the interpretation of the data, and (6) the stage of inference. Based on the results of research on the form of pragmatic politeness imperative in the learning process of students in class VIII SMP Negeri 1 Pondok Kelapa Central Bengkulu consists of nine utterances which implies a pragmatic imperative which consists of commands, requests, insistence, persilaan, solicitation, requests permission, permit, prohibition, and ngelulu. Imperative meaning is marked by a form of politeness in the imperative form of speech commands using particle was the one, -kan, narration imperative requests please use the phrase, speech urging imperative to use speech that is spoken repeatedly, speech tuturannya form is imperative persilaan please, yes, speech imperatively calls to use the phrase of speech !, let imperative allow tuturannya form is right, yes., speech imperative ban on using the phrase do, and speech is imperative ngelulu form tuturannya keep saying but actually the intended meaning is to stop.Kata Kunci: Pragmatic, Politeness Imperative.